Expression of CD69 molecule in Rheumatoid Arthritis Iraqi patients - AL-Hadithi, Hayfaa S. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Rheumatoid arthritis (RA) is an autoimmune disease, where the normal joint tissues attacked by body’s immune system, causing their inflammation. Cluster of Differentiation 69 (CD69) is a human transmembrane C-Type lectin protein encoded by the CD69 gene. It’s expression was induced by activation (in vivo and in vitro) of T lymphocytes and Natural Killer (NK) Cells. As CD69 early activation has been implicated in the pathogenesis of some inflammatory diseases, its expression on peripheral blood T-lymphocytes must be evaluated.Objective: To evaluate the expression of CD69 on peripheral blood T-lymphocytes in RA Iraqi patients. Patients and methods: This study carried out between March 2014 and May 2014. The study involved 40 patients diagnosed with RA attending rheumatology outpatient’s clinic at Baghdad medical city teaching hospital diagnosed clinically and classified according to the 2010 American College of Rheumatology (ACR) and European League Against Rheumatism (EULAR) classification criteria for rheumatoid arthritis, compared to 40 apparently healthy individuals as a control group. Erythrocyte sedimentation rate (ESR) was measured by Westergren method. Flow cytometric immunophenotype analysis applied on T-lymphocytes for measuring the fluorescence intensity of CD3 and CD69 expression on those cells.Results: This study showed that the mean of ESR in RA patients was (66.8) while in healthy control it is only (20.4). And the mean of CD3 was higher in healthy individuals (41.88) than in RA patients (35.32), while the mean of CD69 was significantly higher among RA patients (11.09) than that of healthy controls (3.58). Also a moderately strong positive linear correlation was found between CD69 expression and RA severity.Conclusions: the expression of CD69 was up-regulated in freshly isolated peripheral blood lymphocytes from RA patients in comparison to healthy individuals.